Monitoring Welfare and Perceptions in South Sudan 2012–2014 : Findings from the High Frequency South Sudan Survey - World Bank (Washington, DC, 2015)
Since early 2012, the World Bank’s High Frequency South Sudan Survey has collected a panel data set to monitor the welfare and perceptions of citizens in a selected number of state capitals in South Sudan. This note presents the findings of all six rounds of the survey on the topics of (1) Security, (2) Economic Conditions, (3) Assets and Consumption, and (4) Access to Services. The results are based on 143 households in Juba, Wau and Rumbek revisited six times. The analysis is restricted to households present in all rounds and, thus, is not statistically representative but only provides a descriptive narrative of the livelihood of the selected urban households in Juba, Rumbek and Wau. These cities are not among the cities most affected by the conflict.